Study bacteriocin produced by strain Lbm.acidophilus К-3 chosen from kumys (Experimental biology, 2015)
Kumis is a product of lactic acid and ethanol fermentations. Many lactic acid bacteria synthesize the antibiotic material of protein-peptide nature, having broad spectrum antibacterial actions. Lbm.acidophilus К-3 as high activity strain against pathogenic bacteria was selected from kumys. Reverse-phase high performance liquid chromatography (Varian Pro Star, Australia) was performed for purification peptide antibiotic. Count of the number of amino acids in antibacterial material has shown the contents 12 amino acids. Maximal IR spectra showed eight absorption peaks in the region 998,72, 1132,12; 1674,31; 1794,67; 1851,76; 2832,69; 3257,7 and 3452,54 sm-1. Studies on identifications of the material produced from culture Lbm acidophilus K-3 have proved it belonged to bacteriocin antibiotic. Antibacterial material produced by Lbm acido philus K-3 was stable in рН from 4 to 9 it has been determined also term stable of the peptide antibiotic is proved.
Keywords: Kumis; lactic acid bacteria; antibiotic material; bacteriocin; amino acids; chromatography; IR spectroscopy